2018
DOI: 10.1017/s1366728918000512
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual exposure enhances left IFG specialization for language in children

Abstract: Language acquisition is characterized by progressive use of inflectional morphology marking verb tense and agreement. Linguistic milestones are also linked to left-brain lateralization for language specialization. We used neuroimaging (fNIRS) to investigate how bilingual exposure influences children's cortical organization for processing morpho-syntax. In Study 1, monolinguals and bilinguals (n = 39) completed a grammaticality judgment task that included English sentences with violations in earlier-acquired (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…The two kinds of syntactically erroneous sentences were matched on many dimensions, including verb and noun age of acquisition, written frequency, concreteness, imageability, and familiarity. Bilateral IFG activation differences between the two morphosyntactic conditions is consistent with prior imaging studies of syntactic processing (Brauer & Friederici, 2007;Friederici, 2002;Stromswold, Caplan, Alpert, & Rauch, 1996;Whitehouse & Bishop, 2008) and a more recent study on bilingual children's processing of these errors in English (Arredondo et al, 2019). Grammaticality judgment studies in adults suggest that error detection and sentence judgment might include several steps.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The two kinds of syntactically erroneous sentences were matched on many dimensions, including verb and noun age of acquisition, written frequency, concreteness, imageability, and familiarity. Bilateral IFG activation differences between the two morphosyntactic conditions is consistent with prior imaging studies of syntactic processing (Brauer & Friederici, 2007;Friederici, 2002;Stromswold, Caplan, Alpert, & Rauch, 1996;Whitehouse & Bishop, 2008) and a more recent study on bilingual children's processing of these errors in English (Arredondo et al, 2019). Grammaticality judgment studies in adults suggest that error detection and sentence judgment might include several steps.…”
Section: Discussionsupporting
confidence: 86%
“…Little to nothing is known about the neuro-anatomical bases of processing inflectional morphology marking tense and agreement, nor whether such processing remains differentiated in adults. A recent study on monolingual and bilingual typically developing children (ages 6-12 years) demonstrated lower behavioral accuracy and greater neural activation in the left inferior frontal gyrus (IFG) for English sentences with violations in later acquired (simultaneous tense/agreement) structures than earlier acquired elements of morphosyntax (-ing and to be errors; Arredondo, Hu, Seifert, Satterfield, & Kovelman, 2019). Typically developing children may show adultlike accuracy on judgments of finiteness and tense/agreement around the age of 6 years (Rice, Wexler, & Cleave, 1995), yet the automaticity of these processes and the cortical organization for language continues to develop into adolescence and possibly beyond (Friederici, 2011;Skeide & Friederici, 2016).…”
mentioning
confidence: 99%
“…In addition, research has implicated a positive correlation between language development and SES, making the latter a suitable variable of interest when investigating the effect of music training on aspects of language and sound perception [25,26]. Language development or experience is also correlated with lateralized activity due to bilingual exposure [27], inviting the suggestion that left-lateralization patterns may be enhanced because of higher SES and/or linguistic experience and processing or, even yet, music training. Thus far, however, these separate streams of literature pertinent to the development of brain asymmetry have not been fully integrated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous bilingual neuroimaging studies always measured an individual's brain activity in association with relatively transient language stimuli, such as word processing (e.g., picture naming, Chen et al, 2020) or morpho-syntactic form contrasts (e.g., grammaticality judgment, Arredondo et al, 2019b). This study investigated the effect of L2 processing on children's brain responses in a more ecological and natural situation, hearing sentence stimuli full of prosodic features embedded in the process of picture-book reading.…”
Section: Brain Activation Pattern For Auditory Story Comprehensionmentioning
confidence: 99%
“…Furthermore, the rapid development of neuroimaging technologies – i.e., event-related potential (ERP), magnetic resonance imaging (MRI), functional near-infrared spectroscopy (fNIRS), etc., – has made it possible to depict the relative contribution of bilingual experience to the brain and mind ( Kroll, 2015 ; García-Pentón et al, 2016 ). Using those new techniques, emerging studies have found some general frameworks for the bilingual effect on neural architecture from the perspectives of both functional reorganization ( Abutalebi and Green, 2007 ; Arredondo et al, 2019b ; Li et al, 2019 ) and structural restructuration, such as gray matter density ( Mechelli et al, 2004 ), white matter integrity ( Mohades et al, 2015 ), and cortical thickness ( Klein et al, 2014 ). Thus, neuroplasticity in the bilingual brain should not come as a surprise, given such evidence of experience-based neuroplasticity ( Hernandez et al, 2019 ) as differences in the hippocampi of a taxi driver and a bus driver ( Maguire et al, 2000 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%